Examining the influence of social media and peer environments on motivation, self-regulation, and learning experiences among Indonesian ELLs - Imelda Nursavitri Irianna; Endah Yulia Rahayu; Nunung Nurjati (Universitas Islam Malang, 2026)
This study addresses the limited understanding of how social media and peer environments simultaneously shape English language learning, particularly in terms of their dual impact on learners’ motivation, self-regulation, and learning experiences. While previous research has often emphasized the benefits of digital tools or peer interaction, it has paid less attention to their contradictory effects and the challenges they pose for learners’ emotional well-being and self-regulation. Using a mixed-methods design, this study collected survey data from 51 English language learners (ELLs) across five major cities in Indonesia, followed by in-depth interviews with five participants. Data were analyzed through descriptive statistics and thematic analysis to enable triangulation. The findings reveal that social media enhances motivation, engagement, and language exposure, but also contributes to distraction and emotional strain. Similarly, peer environments promote collaboration and confidence while simultaneously generating anxiety and social pressure. These findings highlight the complex and often contradictory roles of digital and peer-mediated learning environments. This study contributes to the literature by foregrounding the dual impact of these environments and emphasizing the importance of fostering learner self-regulation and emotional well-being. It offers pedagogical implications for the strategic integration of social media and the development of supportive peer networks in English language learning contexts.